Pengaruh Food Quality dan Kesesuaian Harga Terhadap Kepuasan Konsumen (Studi Kasus: Gaembull Korean and Japanese Restaurant Barbeque All You Can Eat Cabang Bintaro) - Regina Dewi Hanifah (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2019)
ABSTRACTThe increase in culinary business in the last few years has become a reinforcement for entrepreneurs in the food and beverage sector. It also forces culinary entrepreneurs to be more creative in offering their main products to compete with other culinary businesses. One of them is the increasing number of restaurants that offer a buffet style concept or commonly known by our society as "All You Can Eat" Restaurant. To be able to differentiate itself from competitors, Gaembull Restaurant chose the Korean and Japanese Barbeque themes to be served to its customers at quite affordable prices with quite a large number of types of food. Of course, with this offer many consumers are interested in this, sometimes consumers must be willing to wait to eat at this restaurant. The purpose of this study is to be able to see The Influence of Food Quality and Price towards Consumer Satisfaction. By using multiple regression analysis methods, f test, t test and looking for the coefficient of determination, the respondents used were 100 consumers of Gaembull Bintaro Branch Restaurant. The results found from this study are the absence of the influence of Food Quality and Price Conformity both simultaneously and partially on Consumer Satisfaction in Gaembull Restaurant.Keywords: Food Quality, Price Match, Consumer Satisfaction, All You Can Eat Restaurants ABSTRAK Peningkatan dalam bisnis kuliner beberapa tahun terakhir menjadi penguat bagi para pengusaha di bidang makanan dan minuman. Hal ini juga memaksa para pengusaha kuliner untuk semakin kreatif dalam menawarkan produk andalannya agar bisa terus bersaing dengan bisnis kuliner lainnya. Salah satunya adalah meningkatnya jumlah restoran yang menawarkan konsep buffet style atau biasa dikenal oleh masyarakat kita sebagai “All You Can Eat” Restaurant. Untuk dapat membedakan dirinya dengan pesaing, Gaembull Restoran memilih tema Korean dan Japanese Barbeque untuk disajikan kepada para pelanggannya dengan harga yang cukup terjangkau dengan jumlah tipe makanan yang cukup banyak. Tentunya dengan penawaran ini banyak konsumen yang tertarik akan hal ini, sehingga seringkali konsumen harus rela menunggu untuk makan di restoran ini. Tujuan dari penelitian ini adalah untuk dapat melihat pengaruh dari Food Quality dan Kesesuaian Harga Terhadap Kepuasan Konsumen. Dengan menggunakan metode analisis regresi berganda, uji f, uji t dan mencari koefisien determinasi, responden yang digunakan adalah 100 orang konsumen Gaembull Restoran Cabang Bintaro. Hasil yang ditemukan dari penelitian ini adalah tidak adanya pengaruh Food Quality dan Kesesuaian Harga baik secara simultan maupun partial terhadap Kepuasan Konsumen di Gaembull Restoran.Keywords: Kualitas Makanan, Kesesuaian Harga, Kepuasan Konsumen, Restoran All You Can Eat